ANALYSIS OF ORGANISATIONAL PERFORMANCE OF NON-PROFIT INSTITUTIONS: THE CASE OF LIFELONG LEARNING INSTITUTIONS IN CROATIA - Zoran Mihanović; Jurica Pavičić; Nikša Alfirević (Economic Review)
This paper discusses the organisational performance of non-profit institutions of lifelong learning and analyses factors constituting performance of non-profit institutions and educational institutions in particular, as well as the level and structure of performance of these institutions. The verification of the research goals is based on the review of literature, which identifies the specific factors of non-profit educational institutions. On the basis of previous research, a valid research instrument, used to measure performance of institutions of lifelong learning, was created. The level and structure of organisational performance of non-profit educational institutions and the verification of research goals are empirically analysed on a random sample of Croatian institutions. It is believed that the research results can assist managers of educational institutions in creating a strategy, leading to the better organisational performance.